Senam Otak (Brain Gym) Berpengaruh Terhadap Tingkat Stres pada Anak Usia Sekolah Kelas V di SD Negeri Pokoh 1 Wedomartani Ngemplak Sleman Yogyakarta - Yunita Dikir; Atik Badi'ah; Lala Budi Fitriana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Learning activities may cause excessive stress IN children. 82.8% of the causes of stress in children in Indonesian are from their very tight routine. Data of the National Commission for Children Protection show an average of 200 cases per month which increases 28%. Brain gym is used as one of the activities to address the issue of stress in children and to improve memory. This research is aimed at identifying the effect of brain gym on stress levels in school-age children of fifth grade at SD Negeri Pokoh 1 Wedomartani Ngemplak Sleman Yogyakarta. This research is a quasi-experimental research with one-group pre and post-test design. The subjects of the research were all fifth grade students at SD Negeri Pokoh 1 Wedomartani Ngemplak Sleman Yogyakarta in 2014, numbering 36 students. Sampling employed a total sampling and data were analyzed using the wilcoxon test. The results showed that the stress level of children before the brain gym given was mostly in the moderate category (50.0%) and after the brain gym given was mostly in the normal category (75.0%). The statistical test using the wilcoxon test generated p-value of 0.000 <0.05. Conclusion, there was a significant effect of brain gym on stress levels before and after treatment in the fifth grade students at SD Negeri Pokoh 1 Wedomartani Ngemplak Sleman Yogyakarta.